Antinociceptive effects of epidural buprenorphine or medetomidine, or the combination, in conscious cats - Steagall, P. V. M.; Millette, V.; Mantovani, F. B.; Gilbert, P.; Luna, Stélio Pacca Loureiro [UNESP]; Duke-Novakovski, T. (Wiley-Blackwell Publishing, Inc, 2009)
The aim of this study was to compare the antinociceptive effects of epidural buprenorphine (EB), epidural medetomidine (EM) or epidural buprenorphine-medetomidine (EBM). Eight cats were studied. Thermal thresholds (TT) were measured by increasing the temperature of a probe placed on the thorax. Mechanical thresholds (MT) were measured through inflation of a modified blood pressure bladder to the cat's forelimb. After baseline measurements, EB (0.02 mg/kg), em (0.01 mg/kg) or half of the doses of each drug (EBM) were administered. Data were analysed using anova (P < 0.05) and 95% confidence interval (CI). TT increased from 30 min to 1 h after EB and at 45 min after EM. MT increased from 45 min to 2 h after EB, from 15 min to 1 h after em and at 30, 45 min and at 2 h after EBM. MT were significantly lower after EB than em at 30 min. TT were above the upper 95%CI from 15 min to 24 h after EB, from 15 min to 4 h after em and from 15 min to 8 h after EBM. MT were above the upper 95%CI from 15 min to 5 h, and at 8, 12 and 24 h after EB, from 15 min to 6 h after em and from 15 min to 6 h and at 12 and 24 h after EBM. All treatments had similar onset. Overall, EB presented longer period of action than EBM and EM. The same magnitude of analgesia was achieved, but with fewer side effects when EBM was compared with EM.